Proton Therapy for Craniopharyngioma — An Early Report from a Single European Centre. Issue 5 (May 2018) - Ajithkumar, T.; Mazhari, A.-L.; Stickan-Verfürth, M.; Kramer, P.-H.; Fuentes, C.-S.; Lambert, J.; Thomas, H.; Müller, H.; Fleischhack, G.; Timmermann, B.
Abstract: Aims: Proton beam therapy (PBT) is being increasingly used for craniopharyngioma. We describe our early outcome of patients treated with PBT. Materials and methods: Between August 2013 and July 2016, 18 patients with craniopharyngiomas were treated with 54 Cobalt Gray Equivalent (CGE) in 30 fractions over 6 weeks at our centre. The early outcome of 16 patients included in a registry study was analysed. Radiological response was assessed by RECIST criteria and the disease- and treatment-related toxicities were scored according to the CTCAE 4.0. Results: All patients are alive at a median follow-up of 32.6 months (range 9.2–70.6 months) from initial diagnosis. The median age at PBT was 10.2 years (range 5.4–46.9 years). One patient progressed 8.7 months after PBT and subsequently had complete resection of the tumour. At a median follow-up of 18.4 months after PBT, five patients remained in complete remission, four in partial remission and seven with stable disease. The most common adverse effects during PBT were grade 1 (cutaneous in seven patients and fatigue in six patients). There were no treatment-related grade 3 toxicities. Conclusions: Our early results are encouraging and comparable with the limited literature on PBT for craniopharyngioma. Highlights: Proton therapy (PBT) is being increasingly used for craniopharyngioma. Encouraging early results of PBT for craniopharyngioma correspond to published data. A systematic evaluation of neurocognitive function before PBT is recommended.